1998
DOI: 10.1038/sj.bjp.0701640
|View full text |Cite
|
Sign up to set email alerts
|

A new selective antagonist of the nociceptin receptor

Abstract: [Phe 1 C(CH 2 -NH)Gly 2 ]NC(1-13)NH 2 has been tested in the electrically stimulated guinea pig ileum and mouse vas deferens, two nociceptin sensitive preparations. The new compound showed per se little or no eect in the two tissues, but it displaced to the right the concentration-response curves of nociceptin in a concentration-dependent manner. Reinscheid et al., 1995) to be the endogenous ligand of the opioid-like orphan receptor (ORL-1). Despite the structural homology of NC and its receptor with the pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
159
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 11 publications
5
159
0
Order By: Relevance
“…Our previous superfusion study on mouse cortex slices had shown that the inhibitory e ect of nociceptin on noradrenaline release was antagonized by the unselective ORL 1 receptor antagonist naloxone benzoylhydrazone (described by Dunnill et al, 1996;Nicholson et al, 1998) and the selective partial ORL 1 agonist [Phe 1 c(CH 2 -NH)Gly 2 ]-nociceptin(1 ± 13)NH 2 (described by Guerrini et al, 1998), suggesting that nociceptin acts via ORL 1 receptors. This view is further supported by our present ®nding that [Tyr 14 ]-nociceptin (identi®ed as a potent ORL 1 receptor ligand by Reinscheid et al, 1995;Berzetei-Gurske et al, 1996;Shimohigashi et al, 1996;Mathis et al, 1997) mimicked the e ect of nociceptin, in a manner sensitive to naloxone benzoylhydrazone.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous superfusion study on mouse cortex slices had shown that the inhibitory e ect of nociceptin on noradrenaline release was antagonized by the unselective ORL 1 receptor antagonist naloxone benzoylhydrazone (described by Dunnill et al, 1996;Nicholson et al, 1998) and the selective partial ORL 1 agonist [Phe 1 c(CH 2 -NH)Gly 2 ]-nociceptin(1 ± 13)NH 2 (described by Guerrini et al, 1998), suggesting that nociceptin acts via ORL 1 receptors. This view is further supported by our present ®nding that [Tyr 14 ]-nociceptin (identi®ed as a potent ORL 1 receptor ligand by Reinscheid et al, 1995;Berzetei-Gurske et al, 1996;Shimohigashi et al, 1996;Mathis et al, 1997) mimicked the e ect of nociceptin, in a manner sensitive to naloxone benzoylhydrazone.…”
Section: Discussionmentioning
confidence: 99%
“…However, it had been di cult to demonstrate the direct activation of the NC-receptor by NC due to the absence of a selective antagonist for this receptor. Recently, a selective competitive antagonist for the NC-receptor, [Phe 1 C(CH 2 -NH)Gly 2 ]nociceptin(1-13)NH 2 ([F/G]NC(1-13)NH 2 ) has been reported by three of us (GC, RG, RB, Guerrini et al, 1998;Calo' et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Taking NC(1-13)NH 2 as a template, a series of analogues were designed and synthesized to study the structure-activity relationship of the N-terminal tetrapeptide of NC [2,3,6,14]. In an attempt to protect NC(1-13)NH 2 from degradation by aminopeptidases, the pseudopeptide [Phe 1 (CH 2 -NH)Gly 2 ]NC(1-13)NH 2 ([F/G]NC(1-13)NH 2 ) was designed [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to protect NC(1-13)NH 2 from degradation by aminopeptidases, the pseudopeptide [Phe 1 (CH 2 -NH)Gly 2 ]NC(1-13)NH 2 ([F/G]NC(1-13)NH 2 ) was designed [1,2]. Studies showed that this pseudopeptide maintains good affinity and shows a variety of activities including antagonist [2,6], partial agonist [10] and agonist [8,11] activities at OP 4 receptor, depending on the tissue preparation. As to the mechanism of the change in chemical terms, the replacement of CO with CH 2 in this pseudopepetide eliminates the possibility of forming hydrogen bonds; at the same time it increases the flexibility of the N-terminal part of the molecule by transforming the amide into an amine function.…”
Section: Discussionmentioning
confidence: 99%